Infinity in Early Modern Philosophy (Cham : Springer International Publishing, 2018)
This volume contains essays that examine infinity in early modern philosophy. The essays not only consider the ways that key figures viewed the concept. They also detail how these different beliefs about infinity influenced major philosophical systems throughout the era. These domains include mathematics, metaphysics, epistemology, ethics, science, and theology. Coverage begins with an introduction that outlines the overall importance of infinity to early modern philosophy. It then moves from a general background of infinity (before early modern thought) up through Kant. Readers will learn about the place of infinity in the writings of key early modern thinkers. The contributors profile the work of Descartes, Spinoza, Leibniz, and Kant. Debates over infinity significantly influenced philosophical discussion regarding the human condition and the extent and limits of human knowledge. Questions about the infinity of space, for instance, helped lead to the introduction of a heliocentric solar system as well as the discovery of calculus. This volume offers readers an insightful look into all this and more. It provides a broad perspective that will help advance the present state of knowledge on this important but often overlooked researched topic.
Chapter1. Introduction (Ohad Nachtomy and Reed Winegar) -- Chapter2. Infinity in Hobbes and Locke (Yitzhak Y. Melamed (Johns Hopkins University)) -- Chapter3. Infinity in Cavendish (David Cunning (University of Iowa)) -- Chapter4. The Scholastic Concept of the Most Perfect and Infinite Being: the Background to Descartes's Meditations (Igor Agostini (Università del Salento)) -- Chapter5. Descartes' Distinction between the Infinite and the Indefinite (Anat Schechtman (University of Wisconsin, Madison)) -- Chapter6. Descartes on the Infinity of Space vs. Time (Geoffrey Gorham (Macalester College)) -- Chapter7. Spinoza's Taxonomy of the Infinite and its Role in Undoing Human Bondage (Sanja Särman (Hong Kong University)) -- Chapter8. The Road to Finite Modes in Spinoza's Ethics (Noa Shein (Ben-Gurion University)) -- Chapter9. Actual Infinity in Leibniz (Richard Arthur (McMaster)) -- Chapter10. An Unfinished Business: Leibniz and Regis on the World's Infinity (Mogens Laerke (CNRS, ENS Lyon)) -- Chapter11. Leibnizian Encounters with Infinity: Galileo to Spinoza (Ohad Nachtomy (Bar-Ilan/Institute for Advanced Study)) -- Chapter12. The Myth of the Infinite Given Magnitude (Paul Guyer (Brown University)) -- Chapter13. Actual Infinity in Kant (Reed Winegar (Fordham University)).
Religion and Philosophy
text file PDF
Keywords: Philosophy; History, Modern; Mathematics; History; Epistemology; Religion-Philosophy.